Determination on the Success of Cataract Surgeries by Using Sight Restoration Rate (SRR) - Angelo Doniho; Angela Shinta Dewi Amita; Cisca Kuswidyati; Devina Permatasari; Andrew Adiguna Halim (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
The prevalence of blindness in Nusa Tenggara Timur (NTT) reaches 1.0% and the ratio of blindness to ophthalmologist reaches 1:8000. This data means NTT is a place which has vision issues. Blindness is caused by cataract. Untreated cataracts can reduce the productivity of patients and his/her caretaker for quite a long time. Cataract surgery will not only cure the patient’s blindness, but it will also improve the local economy if it is sustainable and on time. Lack of human resources, funds, and medical equipment are the major problems for performing cataract surgery in this area. The cataract surgery is performed at Elisabeth Lela Hospital. Visual acuity is performed before the surgery and 21-35 days after the surgery. The last step is calculating the Sight Restoration Rate (SRR) of all patients. Cataract surgery was conducted to 92 eyes. the SRR of all patients is 46.7%. There are four eyes (4.34%) with post-operative visual acuity <3/60.